On Multiple Interpolation Functions of the q-Genocchi Polynomials - Sun-Jung Lee; Eun-Jung Moon; Seog-Hoon Rim; Jeong-Hee Jin (Journal of Inequalities and Applications, 2010)
Recently, many mathematicians have studied various kinds of the q-analogue of Genocchi numbers and polynomials. In the work (New approach to q-Euler, Genocchi numbers and their interpolation functions, “Advanced Studies in Contemporary Mathematics, vol. 18, no. 2, pp. 105–112, 2009.”, Kim defined new generating functions of q-Genocchi, q-Euler polynomials, and their interpolation functions. In this paper, we give another definition of the multiple Hurwitz type q-zeta function. This function interpolates q-Genocchi polynomials at negative integers. Finally, we also give some identities related to these polynomials.